An Analysis of How Sustainability Performance Influences Financial Performance: Evidence From Türkiye - Gürel, Esra B. Bulgurcu; Atasever, Gülbahar; Gürel, Eymen (International Review of Management and Marketing, 2025)
Today, negative developments such as the rapid depletion and pollution of scarce natural resources, deforestation, and global warming have significantly increased stakeholder awareness. Increased awareness has driven businesses to adopt ethical, environmentally responsible practices and prioritize sustainability. In this context, the aim of this study is to examine the relationship between corporate sustainability and financial performance within the scope of companies listed on the BIST 30 index, which is regarded as a significant indicator of sustainability in Türkiye. Furthermore, firm size is incorporated into the analysis as a control variable. As a result of the analysis, it was found that in the static model, companies included in the XUSRD sustainability index have a positive effect on asset and sales returns. On the other hand, when the inclusion in the XUSRD and XSD25 indexes is evaluated together with firm size, the presence of a negative effect on financial sustainability in the dynamic model limits this positive impact. Additionally, it was determined that firm size alone has a positive effect on financial sustainability.